From colossal magnetoresistance to solar cells: An overview on 66 years of research into perovskites (Phys. Status Solidi A 9∕2017). Issue 9 (8th September 2017) - Wagner, Patrick; Wackers, Gideon; Cardinaletti, Ilaria; Manca, Jean; Vanacken, Johan
Abstract : In this review article, Wagner et al. (Article No.201700394 ) shed light on a multi‐functional family of materials known as "the perovskites", which are all derived from CaTiO3 . Smart modifications in structure and composition result in a plethora of special features, including magnetism, superconductivity, catalytic‐, and photovoltaic activity. To say it with a proverb: Perovskites are like old dogs that learn easily new tricks and, surprisingly, this is ongoing since almost 70 years.